2015
DOI: 10.1007/s40435-015-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Passenger seat vibration control of a semi-active quarter car system with hybrid Fuzzy–PID approach

Abstract: In this paper, semi-active quarter car system with three degrees of freedom is considered for modeling and evaluation of passenger ride comfort. Experimental results of magneto-rheological shock absorber are modeled using polynomial model. The considered algorithms in semi-active quarter car suspension system include PID controller, fuzzy logic controller, hybrid fuzzy-PID controller and hybrid fuzzy-PID controller with coupled rules. Simulation responses of the controlled semi-active and uncontrolled quarter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The primary contribution of this paper lies in the application of a fuzzy combination of fuzzy and fuzzy self-tuning PID controllers. A quarter car model with MR damper with three degrees of freedom (3DOF) is formulated for each uncontrolled, fuzzy controlled, HFPID controlled as proposed by (Singh & Aggarwal, 2017) and HFFPID controlled systems. The model is examined for two kinds of excitations, namely those generated by a bump road and random road profiles, by using Simulations are carried out by Matlab/ Simulink software.…”
Section: Introductionmentioning
confidence: 99%
“…The primary contribution of this paper lies in the application of a fuzzy combination of fuzzy and fuzzy self-tuning PID controllers. A quarter car model with MR damper with three degrees of freedom (3DOF) is formulated for each uncontrolled, fuzzy controlled, HFPID controlled as proposed by (Singh & Aggarwal, 2017) and HFFPID controlled systems. The model is examined for two kinds of excitations, namely those generated by a bump road and random road profiles, by using Simulations are carried out by Matlab/ Simulink software.…”
Section: Introductionmentioning
confidence: 99%
“…The block diagram of the FLST-PID is shown in Figure 2. [14,18,27,28], the trial and error method and the experience of the authors and are shown in Figure 3. The state variables, sprung mass velocity and accelerations used in this work are measured by using velocity sensors or accelerometers.…”
Section: Controller Design For the Semi-active Seat Suspensionmentioning
confidence: 99%
“…Singh and Aggarwal [14] analysed the passenger seat vibration of the semi-active quarter car model with a hybrid Fuzzy-PID control. They reported that the proposed Fuzzy-PID approach offered a better performance in terms of passenger seat acceleration and displacement.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic differential equation of the vertical motion of four unsprung mass is listed as shown in equation (3).…”
Section: Dynamic Differential Equationmentioning
confidence: 99%
“…Ren et al presented an adaptive hybrid control algorithm combined with the ground-hook and skyhook control strategies based on quarter car model of semiactive suspension and designed an unscented Kalman filter to estimate the suspension states [2]. Singh and Aggarwal designed a hybrid Fuzzy-PID controller to evaluate the passenger ride comfort based on a semiactive quarter car model having MR shock absorber [3]. Du et al presented an approach in designing a robust controller for half-car model active suspensions considering changes in vehicle inertial properties, such as the suspension deflection limitation and the controller saturation problem [4].…”
Section: Introductionmentioning
confidence: 99%